Kajian Placemaking Selasar Malioboro Sebagai Tempat Istirahat Wisatawan Yang Baru Tiba Via Stasiun Yogyakarta - Nauval Akmal Lutfi; Hanif Budiman; Nabila Salma F (Jurnal Riset Multidisiplin Edukasi, 2025)
Placemaking is a planning and design approach aimed at developing public spaces to be more attractive, functional, and beneficial for society. It aims to create better environments and social interaction. Selasar is a location or road that connects a street with another in a city. Some cities create specific types of spaces, such as the new Selasar Malioboro in Yogyakarta, which was developed as part of the PT.Kereta Api Indonesia program on March 1, 2021. This new space is intended to improve the existing public spaces in Yogyakarta, ensuring that new and existing spaces are considered as valuable. To implement this, qualitative research methods such as field observations, active data collection, and literature surveys are used, along with Human Centered Urban Design.